Little Einsteins. Mission celebration! - Huang, Erica; Pompey, Aiden; Schwartz, Jesse; Wojcik, Natalia (Burbank, CA : Buena Vista Home Entertainment, 2006)
The four Little Einsteins climb aboard their musical ship Rocket for a world-wide adventure.
Features: interactive game.
Voices: Erica Huang, Aiden Pompey, Jesse Schwartz, Natalia Wojcik.
Originally broadcast on television 2005-2006.
Preschool.
DVD, Dolby digital 5.1 surround.
In English, French, or Spanish.
Keywords: Travelers -- Juvenile films; Adventure and adventurers -- Juvenile films; Television programs; Travelers -- Drama; Adventure and adventurers -- Drama; Television programs; Children's television programs